2014
DOI: 10.1080/02642069.2014.886193
|View full text |Cite
|
Sign up to set email alerts
|

Human capital, diversity, and new firm formation

Abstract: This paper analyses the role of human capital in determining regional variations in firm births. It is argued that both the level and heterogeneity of human capital are particularly important for services. This is confirmed by an empirical analysis of data for sub-regions of Great Britain from 2001 to 2007 utilising ordinary leastsquares and maximum likelihood models incorporating spatial effects. Other variables found to impact on the creation of new service firms are related to labour market effects, agglome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Fourth, human capital and entrepreneurship, defined in terms of new venture creation, are linked through a number of channels (Bishop and Brand ): (a) Opportunity recognition and exploitation. According to the human capital theory, once engaged in the entrepreneurial process, individuals with more or higher quality human capital should have superior ability in successfully exploiting opportunities (Davidsson and Honig ); (b) Enhance knowledge spillovers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Fourth, human capital and entrepreneurship, defined in terms of new venture creation, are linked through a number of channels (Bishop and Brand ): (a) Opportunity recognition and exploitation. According to the human capital theory, once engaged in the entrepreneurial process, individuals with more or higher quality human capital should have superior ability in successfully exploiting opportunities (Davidsson and Honig ); (b) Enhance knowledge spillovers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…More than three decades ago, several authors showed evidence for a positive effect of the degree of specialization of workers on the generation of positive externalities and economic growth [140,144]. A good example of this could be the firms belonging to the clusters of ham industry located in the "Emilia-Romagna" area, which workers have proved to be clearly more productive than those belonging to other geographically dispersed companies [57] In addition, inasmuch as it encompasses a full set of knowledge and skills, which are necessary to detect and tap into new opportunities, human capital plays an essential role in entrepreneurship [9]. According to Reference [145], there is a shortage of employee talent in the food industry in Spain, affecting 46% of companies.…”
Section: Knowledge and Entrepreneurship In Clustersmentioning
confidence: 99%
“…Recently, the relationship between entrepreneurship and economic growth has acquired particular relevance in both the academic and policy scene [9]. The growth of economic output implies an increase in regional demand and a rise in the general level of entrepreneurial opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…A second factor that may exhibit spatial stickiness is knowledge capital. Recent research has argued that that knowledge capital is critical for entrepreneurship as it has a high propensity to spillover from existing firms, thus providing opportunities for nascent entrepreneurs to exploit (Bishop and Brand, 2014;Bishop, 2012). Such spillovers have a regional dimension if proximity reduces the cost of transmission, thereby promoting information flows between local agents.…”
Section: Regional Entrepreneurship Persistence and Resiliencementioning
confidence: 99%